Research governance and scientific knowledge production in The Gambia - Ozor, Frederick U. (South African Journal of Science, 2014)
Public research institutions and scientists are principal actors in the production and transfer of scientific knowledge, technologies and innovations for application in industry as well for social and economic development. Based on the relevance of science and technology actors, the aim of this study was to identify and explain factors in research governance that influence scientific knowledge production and to contribute to empirical discussions on the impact levels of different governance models and structures. These discussions appear limited and mixed in the literature, although still are ongoing. No previous study has examined the possible contribution of the scientific committee model of research governance to scientific performance at the individual level of the scientist. In this context, this study contributes to these discussions, firstly, by suggesting that scientific committee structures with significant research steering autonomy could contribute not only directly to scientific output but also indirectly through moderating effects on research practices. Secondly, it is argued that autonomous scientific committee structures tend to play a better steering role than do management-centric models and structures of research governance.